Continuous treatment with FTS confers resistance to apoptosis and affects autophagy. - Eran Schmukler; Eya Wolfson; Zvulun Elazar; Yoel Kloog; Ronit Pinkas-Kramarski (PLoS ONE)
High percentage of human cancers involves alteration or mutation in Ras proteins, including the most aggressive malignancies, such as lung, colon and pancreatic cancers. FTS (Salirasib) is a farnesylcysteine mimetic, which acts as a functional Ras inhibitor, and was shown to exert anti-tumorigenic effects in vitro and in vivo. Previously, we have demonstrated that short-term treatment with FTS also induces protective autophagy in several cancer cell lines. Drug resistance is frequently observed in cancer cells exposed to prolonged treatment, and is considered a major cause for therapy inefficiency. Therefore, in the present study, we examined the effect of a prolonged treatment with FTS on drug resistance of HCT-116 human colon cancer cells, and the involvement of autophagy in this process. We found that cells grown in the presence of FTS for 6 months have become resistant to FTS-induced cell growth inhibition and cell death. Furthermore, we discovered that the resistant cells exhibit altered autophagy, reduced apoptosis and changes in Ras-related signaling pathways following treatment with FTS. Moreover we found that while FTS induces an apoptosis-related cleavage of p62, the FTS-resistant cells were more resistant to apoptosis and p62 cleavage.